Effect of mood manipulation on physiological variables during submaximal exercise - Lickliter, K. L.; Ogles, B. M.; Heath, E. M. (Medicine & Science in Sports & Exercise, 1996)
The effect of mood manipulation on physiological variables at 65% of VO2max running intensity was assessed. Three separate tests following one of three mood-induction classes (bad, neutral, good) were conducted. Mood induction was achieved by having Ss read 60 cards with printed statements. Directly after mood-induction the Profile of Mood States (POMS) was completed. A statistical analysis showed that the POMS varied significantly with the mood that was induced. VO2 was also significantly different between the three mood states. It was highest under the "good" mood which was significantly different to both the neutral and bad mood conditions. Heart rates and RPE did not differ between the mood conditions. Implication: A positive or a "good" mood will facilitate the utilization of more of the aerobic capacity in submaximal exercise than either a "neutral" or "bad" mood even though an athlete might not report any difference. The mental state of an exercising athlete has considerable influence on the degree to which the body's resources are used. Being in a good mood (e.g., positive, confident, high self-efficacy) will establish conditions for better performances.